Programmatic Approach to Management of Tetralogy of Fallot With Major Aortopulmonary Collateral Arteries: A 15-Year Experience With 458 Patients. (April 2017) - Bauser-Heaton, Holly; Borquez, Alejandro; Han, Brian; Ladd, Michael; Asija, Ritu; Downey, Laura; Koth, Andrew; Algaze, Claudia A.; Wise-Faberowski, Lisa; Perry, Stanton B.; Shin, Andrew; Peng, Lynn F.; et al.
Abstract : Background—: Tetralogy of Fallot with major aortopulmonary collateral arteries is a complex and heterogeneous condition. Our institutional approach to this lesion emphasizes early complete repair with the incorporation of all lung segments and extensive lobar and segmental pulmonary artery reconstruction. Methods and Results—: We reviewed all patients who underwent surgical intervention for tetralogy of Fallot and major aortopulmonary collateral arteries at Lucile Packard Children's Hospital Stanford (LPCHS) since November 2001. A total of 458 patients underwent surgery, 291 (64%) of whom underwent their initial procedure at LPCHS. Patients were followed for a median of 2.7 years (mean 4.3 years) after the first LPCHS surgery, with an estimated survival of 85% at 5 years after first surgical intervention. Factors associated with worse survival included first LPCHS surgery type other than complete repair and Alagille syndrome. Of the overall cohort, 402 patients achieved complete unifocalization and repair, either as a single-stage procedure (n=186), after initial palliation at our center (n=74), or after surgery elsewhere followed by repair/revision at LPCHS (n=142). The median right ventricle:aortic pressure ratio after repair was 0.35. Estimated survival after repair was 92.5% at 10 years and was shorter in patients with chromosomal anomalies, older age, a greater number of collaterals unifocalized, and higher postrepair right ventricle pressure. Conclusions—: Using an approach that emphasizes early complete unifocalization and repair with incorporation of all pulmonary vascular supply, we have achieved excellent results in patients with both native and previously operated tetralogy of Fallot and major aortopulmonary collateral arteries. Abstract : Supplemental Digital Content is available in the text.